Implementasi E-Learning dalam Pembelajaran IPA Era Pandemi Covid-19 di MI Al-Fattah Dukutalit Juwana - Nur Aziz Amalia Khaq; Lailatul Fitriyah; Hesti Malinda (JEID: Journal of Educational Integration and Development, 2021)
The purpose of this study was to determine the implementation of E-Learning in science learning at MI Al-Fattah Dukutalit Juwana during the Covid-19 pandemic era. The method in writing is a qualitative descriptive method, then searches for the most relevant and main data related to the study of the implementation of E-Learning in science learning in the midst of the Covid 19 pandemic. The results showed that the implementation of E-Learning in science learning went well. The implementation of learning during the Covid-19 pandemic uses applications as support in learning, namely by using the google classroom, youtube, and WhatsApp applications. As well as problems in the implementation of E-Learning learning during the Covid pandemic at MI Al-Fattah Dukutalit Juwana, including communication networks from students such as signal difficulties, limited quotas owned by students, measurement of affective and psychomotor assessments of students, and lack of motivation from parents to children . Some solutions to overcome existing problems include reducing the assignment given, giving explanations to parents so that children remain enthusiastic and providing internet quota from the school to students.